Disordered brownmillerite Ba2InCeO5+delta with enhanced oxygen reduction activity - Jijil, Chamundi P.; Unni, SreeKuttan M.; Sreekumar, Kurungot; Devi, R. Nandini (Chemistry of Materials, 2012)
A disordered brownmillerite, Ba2InCeO5+delta, with slight tetragonal distortion from ideal cubic perovskite is synthesized and its oxygen reduction reactivity tested. The material displayed oxygen reduction behavior in alkaline solution comparable to that of standard 40 wt % Pt/C catalyst and attractive activity characteristics which renders it a potential system for low temperature fuel cell applications.
Keywords: brownmillerite; fuel cell; oxygen reduction reaction; Rietveld refinement

In situ encapsulation of ultra small ceria nanoparticles stable at high temperatures in the channels of mesoporous silica - Ghosh, Sumona; Jijil, Chamundi P.; Devi, R. Nandini (Microporous and Mesoporous Materials, 2012)
Ultra small ceria nanoparticles of sizes <2 nm stable at 500 degrees C are encapsulated in the channels of mesoporous silica by employing a novel method of synthesis. The method involves modifying non-ionic polymer templates with ionic surfactants to enhance anchoring of metal ion precursors. In this way, further silica wall formation around the template ensures isolation of the nanoparticles exclusively within the channels after template removal by heat treatment. Further understanding of the interaction of the composite template system and cerium precursor is gained by cyclic voltammetric studies. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: ceria; Encapsulation; Mesoporous silica; Template synthesis

Noble metal ions incorporated in lattice points of perovskites - water gas shift activity of BaCe1-xPtxO3-d - Jijil, Chamundi P.; Rajarajan, A. K.; Devi, R. Nandini (56th DAE-Solid State Physics Symposium (SSPS), 2012)
Recently precious metals supported on oxides were reported to be very promising catalysts for the lower-temperature WGS reaction. Here we report the synthesis of platinum doped barium cerate and its use as catalysts for WGS reaction. It has been found that maximum CO conversion was obtained at 350 degrees C which enhanced after the first cycle. XPS analysis shows that after the first cycle more ionic Platinum species are present on the surface of the catalyst. Neutron diffraction at room temperature shows that the oxygen vacancies are in the O2 position and increases with increasing Pt substitution.
Keywords: BaCeO3; Neutron diffraction; Platinum catalysis; WGS reaction

Effect of b site coordination environment in the ORR activity in disordered brownmillerites Ba2In2-xCexO5+delta - Jijil, Chamundi P.; Bhange, Siddheshwar N.; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2015)
Ba2In2O5 brownmillerites in which the In site is progressively doped with Ce exhibit excellent oxygen reduction activity under alkaline conditions. Ce doping leads to structural changes advantageous for the reaction. Twenty-five percent doping retains the ordered structure of brownmillerite with alternate layers of tetrahedra and octahedra, whereas further increase in Ce concentration creates disorder. Structures with disordered oxygen atoms/vacancies are found to be better oxygen reduction reaction catalysts probably aided by isotropic ionic conduction, and Ba2In0.5Ce1.5O5+delta is the most active. This enhanced activity is correlated to the more symmetric Ce site coordination environment in this compound. Stoichiometric perovskite BaCeO3 with the highest concentration of Ce shows very poor activity emphasizing the importance of oxygen vacancies, which facilitate O-2 adsorption, in tandem with catalytic sites in oxygen reduction reactions.
Keywords: brownmillerite; fuel cell; oxygen disorder; oxygen reduction reaction; Rietveld refinement

Nitrogen doping in oxygen-deficient Ca2Fe2O5: a strategy for efficient oxygen reduction oxide catalysts - Jijil, Chamundi P.; Lokanathan, Moorthi; Chithiravel, Sundaresan; Nayak, Chandrani; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Babu, P. D.; Kakade, Bhalchandra A.; Devi, R. Nandini (ACS Applied Materials and Interfaces, 2016)

Mechanical activation in reduced graphite oxide/boron nitride nanocomposite electrocatalysts for significant improvement in dioxygen reduction - Patil, Indrajit M.; Jijil, Chamundi P.; Lokanathan, Moorthi; Swami, Anita; Kakade, Bhalchandra (Sustainable Energy & Fuels, 2018)
A nanocomposite of reduced graphite oxide (rGO) with hexagonal boron nitride (h-BN) is prepared using a simple hydrothermal method. Significant enhancement in the surface area of the composite is mainly due to the pre-mechanical activation of pristine GO. The structural and morphological study reveals the formation of a homogeneous nanocomposite and masking of rGO sheets over micron sized h-BN particles respectively. Interestingly, the as-synthesized GOBN2-BM composite (nanocomposite of 2 wt% h-BN with mechanically activated GO) catalyst exhibits significant oxygen electroreduction kinetics in terms of onset potential (E-onset = 0.89 V), half-wave potential (E-1/2 = 0.74 V) and limiting current density (J(L) = 4.4 mA cm(-2)) with a single step similar to 4-electron transfer pathway in alkaline medium. Though the composite catalysts exhibit higher overpotential (110 mV) than state-of-the-art Pt/C catalysts, they are much superior to previously reported carbon or h-BN based nanocomposite electrocatalysts. Importantly, the GOBN2-BM nanocomposite shows excellent tolerance towards both methanol oxidation and CO poisoning. Moreover, the nanocomposite catalysts show substantially higher stability than Pt/C catalysts even after 5000 cycles under similar conditions. Additionally, they show a better relative current stability (95% retention) than that of a Pt/C catalyst, signifying immense selectivity and durability towards oxygen electroreduction kinetics. The electrocatalytic oxygen reduction activity of the nanocomposite is mainly attributed to the high surface area (thanks to mechanical activation of GO, leading to increased pore distribution) as well as the synergistic mechanism between the h-BN and carbon network of rGO. Hence, it could be a potential cathode catalyst to replace precious-metal based catalysts in alkaline fuel cells.